Electronic Component Cooling Using Jet Aeration - Muniandy, Vimalanathan (Universiti Sains Malaysia, 2005)
Electronic components play a pivotal part in many industries around the world. They range from the telecommunications industry all the way to the automotive industry. The number of components on a chip has increased many folds and the chip size has decreased through years of research. This is done to ensure more memory can be kept in a computer. But, this has caused an increase of heat generation as there are too many components on a single chip. Thermal management has become very important as the reliability of the component is very important in ensuring greater efficiency. Many electronic component cooling methods have been developed to fasten electronic component cooling. For this project, a method called immersion cooling will be used. However a new way of immersion cooling will be introduced called jet aeration. Jet aerators were used as a device to cool the liquids. The liquids will circulate as one system. The nozzle with a particular velocity of the liquids will hit the water being used. A plunging jet aerator is simply a liquid jet plunging into a pool of liquid and thereby entering the surrounding air into the liquid pool as swarm bubbles. Various sizes of nozzles have been used to investigate the heat dissipated to the air due to the formation of the bubbles. Multi jets were also used to find out whether it can promote better cooling. Comparisons were done through calculations and representations using graphs.